Hydrological and ecological survey of the Matrosskaya River (Paramushir Island, northern Kuril Islands, Sakhalin Region) - T. Yu. Uglovа; G. N. Dzen; A. I. Nikiforov (Известия ТИНРО)
The Matrosskaya, a small river on Paramushir Island (northern Kuril Islands), was surveyed in August 2022. The main hydrological and chemical parameters of the river water are presented; the morphological structure of the river bed and the granulometric composition of bottom sediments are characterized. Potential suitability of the river for the spawning of pacific salmon is discussed.